Fictional realities and criminology: apprehending social reality through narrative fiction - Frauley, Jon (Journal of Theoretical and Philosophical Criminology, 2021)
The purpose of this article is to advance an appreciative critique of Rafe McGregor’s, A Criminology of Narrative Fiction, and to raise some general issues about the intersection of criminology and fiction that have not been adequately dealt with within criminology. The overall argument is that the value of narrative fiction for criminology lies with the allegorical and counter-factual role it might play.